Erratum: Inequality of opportunity in the United Kingdom, 1991–2008 (Journal of Policy Modeling (2019) 41(5) (1026), (S0161893819300845), (10.1016/j.jpolmod.2019.06.001)) - Groot, Loek; van der Linde, Daan; Vincent, Charlotte (Elsevier BV, 2019)
We investigate the extent to which the tax-and-transfer system of the United Kingdom equalizes opportunities for income attainment among citizens. Within the framework of Roemer's theory of equality of opportunity, and using individual data from the British Household Panel Survey from 1991 to 2008, we calculate the tax rates necessary to equalize opportunities for different circumstances. We provide a ranking of these circumstances by the degree to which they influence income attainment. Although pre-fisc equality of opportunity increases over time, the tax rate necessary to equalize opportunities remains higher than the observed tax rate. Only under a relatively high labour supply elasticity the observed UK tax rate fares well in equalizing opportunities for income attainment.
Keywords: Equality of opportunity; Gender; Inequality; Labour supply; Optimal taxation; Taverne; Economics and Econometrics; SDG 5 - Gender Equality